MENTAL HEALTH OF STUDENTS DURING THE COVID-19 PANDEMIC - Mirilović, Nikola; Janković, Janko (Medicinski podmladak, 2023)
In 2019, the world public was confronted with the disease COVID-19 for the first time, when the new SARS-CoV-2 virus was identified in the Chinese city of Wuhan. The pandemic of the new corona virus has led to the biggest public health crisis at the global level in the last hundred years, while a special challenge has been set for professionals who dealing with mental health protection and students who have been particularly affected due to movement restriction measures. The disease COVID-19 is a respiratory infection, and SARS-CoV-2 is a virus from the group of RNA viruses. The incubation period of the virus is between two and fourteen days, and transmission is very easy and fast. The most common symptom of this disease is fever. The COVID-19 disease pandemic had a negative effect on the mental health of students around the world, and female students rated their mental health worse than male students. The main problems with mental health can be classified above all the increased level of depression, anxiety and stress in response to the COVID-19 pandemic. Depression is more common in students who care more about their health, in female students and those with a lower socio-economic status. Also, people who have been in contact with infected people have more serious depressive reactions compared to those who haven’t had such contact. Regarding anxiety reactions, students at the beginning of their studies experience anxiety reactions more often and those reactions are more intense compared to students in the last years of studies. The student population also showed high levels of stress reactions, which occur more often in female students, as well as in those students who come from urban areas. However, mental health problems can be overcome if students are provided with some form of social support or counseling.